2017
DOI: 10.1088/1361-6463/aa9a71
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional electron density characterisation of arc interruption phenomenon in current-zero phase

Abstract: Two-dimensional electron density imaging over free burning arcs and gas-blast arcs was conducted at current zero using highly sensitive Shack–Hartmann type laser wavefront sensors in order to experimentally characterise electron density distributions for the success and failure of arc interruption in the thermal reignition phase. The experimental results under an interruption probability of 50% showed that free burning arcs with axially asymmetric electron density profiles were interrupted with a success ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Since the Shack-Hartmann sensors are capable of visualising 2D electron density distributions from single-shot recordings, the application of Shack-Hartmann sensors is particularly suited for the dynamic behaviour characterisation of the unstable long-gap decaying arc discharges. In addition, by using the Shack-Hartmann sensors, we have also demonstrated the single-shot electron density comparison between success and failure of arc interruption in current-zero phase and concluded that the excellent thermal interruption performance is achieved by adjusting the SF 6 gas blasting for realising the arcs with axially asymmetric shapes and locally reduced electron densities in the arc channels [14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Since the Shack-Hartmann sensors are capable of visualising 2D electron density distributions from single-shot recordings, the application of Shack-Hartmann sensors is particularly suited for the dynamic behaviour characterisation of the unstable long-gap decaying arc discharges. In addition, by using the Shack-Hartmann sensors, we have also demonstrated the single-shot electron density comparison between success and failure of arc interruption in current-zero phase and concluded that the excellent thermal interruption performance is achieved by adjusting the SF 6 gas blasting for realising the arcs with axially asymmetric shapes and locally reduced electron densities in the arc channels [14].…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, these sensors can be utilised for various kinds of arc-quenching media without a theoretical assumption such as local thermodynamic equilibrium [13][14][15][16][17], because they measure a refractive index distribution induced by the electrons in arcs, which is an universal property of discharge plasmas. Therefore, this method is also applicable to feasibility study of the recently proposed SF 6 alternative gases, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the actual interrupter chamber boundary situation, the paper mainly follows the following treatment to give the boundary conditions of each equation variable on the calculation model. To make all control equations closed, the following boundary conditions are used [28].…”
Section: Simulation Model and Boundary Conditionsmentioning
confidence: 99%